2013
DOI: 10.1007/s00436-013-3275-9
|View full text |Cite
|
Sign up to set email alerts
|

Livestock trypanosomosis in Uganda: parasite heterogeneity and anaemia status of naturally infected cattle, goats and pigs

Abstract: The prevalence and pathogenic effects of trypanosomosis were determined in cattle, goats and pigs reared in Kasese, Jinja and Rakai districts, Uganda; presence of trypanosomes was detected by buffy coat technique (BCT). The overall prevalence of trypanosomosis in cattle was 7.6% (144/1,891), 0.7% in goats (4/573) and 2.3% in pigs (9/386). Internal transcribed spacer 1 (ITS1) of ribosomal DNA polymerase chain reaction was utilised to identify trypanosomes to species level and revealed infections in 108 of the 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
20
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 24 publications
12
20
0
2
Order By: Relevance
“…An earlier study by Angwech et al [51] in Amuru and Nwoya districts, which border the study area in the present study, found that T. vivax was also the most predominant trypanosome species in cattle. Our results are also consistent with several other previous studies on tsetse and trypanosomes ecology in Uganda [39,52,53].…”
Section: Discussionsupporting
confidence: 93%
“…An earlier study by Angwech et al [51] in Amuru and Nwoya districts, which border the study area in the present study, found that T. vivax was also the most predominant trypanosome species in cattle. Our results are also consistent with several other previous studies on tsetse and trypanosomes ecology in Uganda [39,52,53].…”
Section: Discussionsupporting
confidence: 93%
“…Trypanosoma b. brucei is found in various domestic ungulates but it is particularly virulent in dogs, camels and horses, the latter often succumbing to infection within a few months in the absence of treatment. In areas where more than one trypanosome species is present, mixed infections in domestic animals are often encountered (Kihurani et al 1994; Auty et al 2008; Biryomumaisho et al 2013; Takeet et al 2013; Moti et al 2015) and modern molecular techniques (Desquesnes and Davila, 2002) facilitate speciation. Many wild animal species in Africa also host one or more trypanosome species and can serve as reservoirs for both human and domestic animal infective trypanosomes (Mulla and Rickman, 1988; Auty et al 2012).…”
Section: The Animal Trypanosomiases: Distribution Transmission Hostmentioning
confidence: 99%
“…Anemia due to hemolysis can be caused by parasites implicated in tick born fever including piroplasms that invade red blood cells like Babesia spp in small (Esmaeilnejad et al, 2012;Yeruham et al, 1998) and large ruminants (Bal et al, 2016;Trueman and Blight, 1978) and Theileria spp in lambs (Alani and Herbert, 1988) and cattle (Omer et al, 2002;Moll et al, 1986) and rickettsiae, mainly Anaplasma spp that infect granulocytes up to 90% in the peak of bacteremia as it is referred in sheep (Yasini et al, 2012), goats (Gokce and Woldehiwet, 1999) and cattles (Ashuma et al, 2013;Henniger et al, 2013). Furthermore, protozoa like Trypanosoma (Biryomumaisho et al, 2013;Katunguka-Rwakishaya et al, 1997;Anosa et al, 1992) and certain Mycoplasma species (Genova et al, 2011;Suzuki et al, 2011) can also be found in plasma and/or in erythrocytes. In addition, microfilaria, the larval stage of stephanofilarial worm, the causative agent of the bovine stephanofilarial dermatitis, enters peripheral blood circulation causing anemia by increasing erythrocytic fragility (Singh et al, 2011).…”
Section: Hemolytic Anemiamentioning
confidence: 99%